2007
DOI: 10.1084/jem.20062342
|View full text |Cite
|
Sign up to set email alerts
|

The length of lipids bound to human CD1d molecules modulates the affinity of NKT cell TCR and the threshold of NKT cell activation

Abstract: CD1d-restricted lymphocytes recognize a broad lipid range. However, how CD1d-restricted lymphocytes translate T cell receptor (TCR) recognition of lipids with similar group heads into distinct biological responses remains unclear. Using a soluble invariant NKT (iNKT) TCR and a newly engineered antibody specific for α-galactosylceramide (α-GalCer)–human CD1d (hCD1d) complexes, we measured the affinity of binding of iNKT TCR to hCD1d molecules loaded with a panel of α-GalCer analogues and assessed the rate of di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

16
276
0
2

Year Published

2010
2010
2018
2018

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 210 publications
(294 citation statements)
references
References 56 publications
(87 reference statements)
16
276
0
2
Order By: Relevance
“…T cell activation is also sensitive to alkyl chain differences in the CD1c-antigen mannosyl-β-phosphomycoketide (MPM), with length, methyl branching pattern and stereoarrangments influencing responses (40). Furthermore, the length of the alkyl chains and lipid saturation of the CD1d-antigen α-galactosylceramide (α-GalCer) is important for controlling CD1d-restricted invariant NKT cell activity (41). Consistent with these reports, our data suggest that communication of structural differences in lipid tails to T cells is a central feature of CD1-lipid antigen presentation.…”
Section: Discussionmentioning
confidence: 99%
“…T cell activation is also sensitive to alkyl chain differences in the CD1c-antigen mannosyl-β-phosphomycoketide (MPM), with length, methyl branching pattern and stereoarrangments influencing responses (40). Furthermore, the length of the alkyl chains and lipid saturation of the CD1d-antigen α-galactosylceramide (α-GalCer) is important for controlling CD1d-restricted invariant NKT cell activity (41). Consistent with these reports, our data suggest that communication of structural differences in lipid tails to T cells is a central feature of CD1-lipid antigen presentation.…”
Section: Discussionmentioning
confidence: 99%
“…It was shown that the iNKT TCR did not have direct contact with the lipid tails of α-GalCer based on the crystal structure of CD1d-α-GalCeriNKT TCR in mice and in humans (20,21). Nevertheless, a series of analogs with the same glycan head as α-GalCer but with different chain length or presence of double bond on either of the two lipid tails would differ in the binding affinity and dissociation rate for human iNKT TCR when complexed with human CD1d (hCD1d) molecule (22).…”
mentioning
confidence: 99%
“…Consequently, polar heads but not hydrophobic tails are assumed to establish stimulatory contacts with TCRs. Nevertheless, modifications in the lipid chains may also indirectly impact on TCR recognition (5).…”
mentioning
confidence: 99%